Catalyst-Free [2,3]-Sigmatropic Rearrangement Reactions of Photochemically Generated Ammonium Ylides - Li, Fang; He, Feifei; Koenigs, Rene M. (Synthesis, 2019)
The rearrangement reaction of ammonium ylides furnishes valuable α,α-disubstituted amino esters. In this work, we describe the visible-light photolysis reaction of aryldiazoacetates in the presence of tertiary amines that react via a free ammonium ylide in a sigmatropic rearrangement reaction to provide amino esters in moderate to very good yields (33 examples, up to 97% yield).
Keywords: photochemistry; diazoalkanes; carbenes; amines; ylides; rearrangement